Part IV Italy: Case 11 Naturns/Naturno - Volgger, Michael; Pichler, S.; Herntrei, M. (2015)
The extant literature distinguishes sharply between corporate and community models of destination governance. In contrast, the case of Naturns/Naturno illustrates how a specific mixture of corporate and community approaches in governance can yield positive results. In particular, it shows how the existence of a network core characterized by integrative entrepreneurial leadership, an element that would in the first instance be associated with a corporate-driven destination, turns out to be a potential driver of a successful community-oriented destination development. In Naturns/Naturno, through its integrative entrepreneurial behavior, a hotel consortium has been influential in leading the transformation of the whole destination toward increased quality, strategic coherence, and innovativeness, while maintaining its community orientation.